Bimetallic Selenide LiInSe2 Decorated with a Uniform Carbon Layer with Superior Lithium Storage Performance. Issue 1 (4th November 2019) - Zhang, Mengqi; Liu, Yangyang; Zhang, Yupeng; Bai, Xue; Zhu, He; Li, Xuesong; Liu, Yang; Cui, Deliang; Li, Bo; Tao, Xutang
Abstract: Owing to their relatively high electronic conductivity and electrochemical activity, bimetallic chalcogenides exhibit promising applications in advanced lithium‐ion batteries. Herein, for the first time, a uniform thin carbon layer (about 2–3 nm) derived from citric acid coating bimetallic selenide, LiInSe2, is designed. When used as an anode material for lithium‐ion batteries, the novel carbon‐coated LiInSe2 anode delivers high initial charge/discharge capacities of 545.2/732.0 mAh g −1 at a current density of 100 mA g −1 . Even after 800 cycles at 1500 mA g −1, a high reversible capacity of 333 mAh g −1 can be achieved, suggesting its superior rate capability and cycling stability. The excellent electrochemical performance of the carbon‐coated LiInSe2 anode is ascribed to the improved electronic/ionic conductivity, electrochemical activity, and reaction kinetics. This remarkable lithium storage property indicates the potential application of bimetallic selenide for future lithium‐ion batteries. Abstract : The uniform carbon layer (about 2∼3 nm) derived from citric acid coating bimetallic selenide LiInSe2 composite is designed. When employed as an anode material for lithium storage, the novel carbon coated LiInSe2 anode delivers superior electrochemical performance, including improved cycling stability and enhanced rate capability, and shows a reversible capacity of 333 mAh g −1 after 800 cycles at 1500 mA g −1 .